Verification of Academic Buoyancy Scale for Adolescents in Indian Context - Kumar, Vijay; Sharma, Komal (International Journal of Psychosocial Rehabilitation, 2020)
Academic buoyancy is a psycho-educational concept. Martin (2009), proposed academic buoyancy as a way of exploring the constructive responses of different setbacks and difficulties, which is experienced by the students in their everyday school or academic life such as pressure of examination, obtaining poor grades or marks, complex schoolwork, minor negative interactions with teachers and competing deadlines. The main purpose of the present paper was to adapt the academic buoyancy scale and to investigate its psychometric properties in terms of reliability and factor structure in the Indian context. Sample was taken from 400 senior secondary school students from different districts of Punjab, India. For investigating the validity of test, EFA was used and CFA was used to verify how well the numbers of factors associated with construct as well as internal consistency was assessed by Cronbach’s alpha. The result shows that the hypothesized uni-dimensional model was found to provide an excellent fit to the collected data from the present sample.